2020
DOI: 10.1038/s41598-020-73245-3
|View full text |Cite
|
Sign up to set email alerts
|

Projections of heat stress and associated work performance over India in response to global warming

Abstract: Summertime heat stress future projections from multi-model mean of 18 CMIP5 models show unprecedented increasing levels in the RCP 4.5 and RCP 8.5 emission scenarios over India. The estimated heat stress is found to have more impact on the coastal areas of India having exposure to more frequent days of extreme caution to danger category along with the increased probability of occurrence. The explicit amount of change in temperature, increase in the duration and intensity of warm days along with the modulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 80 publications
2
26
0
Order By: Relevance
“…The occurrence of humid‐heat during the planting and early growing season (e.g., NFSM, n.d. ), which is typically labor‐intensive, puts agricultural workers at heightened risk of heat‐related illnesses and can reduce work performance (Koteswara Rao et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of humid‐heat during the planting and early growing season (e.g., NFSM, n.d. ), which is typically labor‐intensive, puts agricultural workers at heightened risk of heat‐related illnesses and can reduce work performance (Koteswara Rao et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Some monsoonal regions such as South Asia, experience the most humid-heat events in May before the typical monsoon season (June-September) or early in the monsoon season. The occurrence of humid-heat during the planting and early growing season (e.g., NFSM, n.d.), which is typically labor-intensive, puts agricultural workers at heightened risk of heat-related illnesses and can reduce work performance (Koteswara Rao et al, 2020).…”
Section: Extreme Heat Seasonal Timingmentioning
confidence: 99%
“…Anthropogenic warming and increased agriculture in India have caused a rise in moist heat extremes in the recent period (Mishra et al., 2020). Such extremes are also projected to increase over the region resulting in a 40% decline in the work performance by the end of the century (Koteswara Rao et al., 2020). With rising TC intensities and heat stress posing increased destruction and mortality, it is necessary to examine these events from a compound events perspective.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of multiple variables at high spatial and temporal resolutions is crucial for examining the impact of temporally compounding TC‐Heat stress events. The reanalysis data set has been widely used for the assessment of moist heat stress (Koteswara Rao et al., 2020; Matthews et al., 2017; Mishra et al., 2020) and TC impact (Matthews et al., 2019; Messmer & Simmonds, 2021; Owen et al., 2021; Rajeev & Mishra, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Koteswara Rao et al. ( 2020 ) projected a 30%–40% decline in the work performed in India by the end of the century due to elevated heat stress levels. A study of the Zayandehroud River route from 2014 to 2039 showed that some tourism destinations in the western part of the river are at risk of a reduction in the number of climate comfort days under the increasing climate comfort index (Yazdanpanah et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%